An Evaluation of Four-Year B.Ed. Programme of Tribhuvan University - Khanal, Sharada; Awasthi, Jai Raj (Siddhajyoti Interdisciplinary Journal, 2026)
This study evaluated the four-year B.Ed. program in English Language Teaching offered by Tribhuvan University, using Stufflebeam’s CIPP evaluation model (1983). The study used the qualitative research design. The courses were examined and evaluated from the viewpoints of teachers in the four-year B.Ed. program and the students who completed it. Data are gathered through interview guidelines with four participants. It was based on the CIPP model evaluation checklist. The study found that the course effectively addressed the needs of secondary-level English language teachers. However, there is an obvious gap between theoretical knowledge and its connection to the real world. Both teachers and students found the course objectives very realistic, but failure to address the modern trend of adopting information communication technology, along with a disconnection between language skill development and objectives. It is necessary to reform the curriculum through digital integration, career counseling, teacher professional development, and monitoring.